Cartografia docente: alinhavos entre imagens, experiências e naturezas na formação de professores de ciências e biologia - Silva, João Paulo dos Santos (2019)
This cartographic research emerges from the concerns and crossings made possible by the investigations and unfoldings of my monographic work. In this new adventure, eleven teachers of Biological Sciences embarked with me, and all of us have participated in the curricular component of Image of Nature in Teaching Science between 2010 and 2012. Inspired by the idea of device proposed by Focault, we seek to create maps, images, narratives and technologies to think about our process of teaching (trans)formation. We used the video-mosaics of nature images, produced in the curricular component, as tools to think about the (trans)formation processes that have occurred since then. The mosaic, taken as a device, leads us to another look, provoking tensions in our trajectories towards the aesthetics of being teacher. The logbook, another device of this cartography, is born and traverses us as a record of the complex dynamics established between the discourse and the emergent realities of it. Forged as plans of subjectivities, possibilities and walks through different worlds, teacher maps trace and involve processes of singularization towards aesthetics of professorialities. The idea of ​​a teacher map even emerges from our need to delimit these maps in front of other devices that we used during the cartographic process, other possible mappings in which we invest. In addition, the new video mosaic of imagery experiments, with traces of the experiences lived in this research, aligned the crossings of this process to what we call teacher cartography. What began as something unpretentious with the first productions of the mosaics of nature images in 2010 persists in renewing itself. The new video mosaic of imagery experiences of nature brings with it a trajectory that is not restricted to the university, much less to the curriculum component 'Images of Nature'. A collective walking that we are passing by, leaving spores and creating rhizomes that are scattered around the world. Finally, elements that make us look at how many different paths have brought us here, which often deterritorialized us, have transgressed into horizons even imagined. Paths that seemed fixed, stable and eternal, but which are devastated by something, often what becomes an (in) experience. The power of this cartographic process has led us to cultivate other senses about our process of (trans)formation, visiting territories not so distant and that are present in our becoming teacher, establishing relations not only between the student of yesteryear, but also the teacher of today.